A CROSS-SECTIONAL STUDY ON THE ROLE OF DIAGNOSTIC LAPAROSCOPY IN IDENTIFYING TUBAL AND PERITONEAL FACTORS IN FEMALE INFERTILITY. - Gupta, Beena; Bhagat, Prabhat Kumar (Student's Journal of Health Research Africa, 2024)
Background Infertility affects a significant percentage of couples worldwide, with tubal and peritoneal factors being major contributors. While hysterosalpingography (HSG) is commonly used for assessing tubal patency, its limitations in accuracy make diagnostic laparoscopy a preferred choice. Laparoscopy allows direct visualization of the pelvic organs, providing a more accurate diagnosis of tubal blockages and peritoneal pathologies, such as adhesions and endometriosis, which are often undetectable through non-invasive techniques. The study aims to evaluate the role of diagnostic laparoscopy in identifying tubal and peritoneal causes of infertility in female patients. Methods A cross-sectional study was conducted on 50 women with primary or secondary infertility. Each participant underwent diagnostic laparoscopy following clinical evaluation and HSG. Data were collected on tubal blockages, peritoneal adhesions, and endometriosis, and results were analyzed to compare findings between primary and secondary infertility groups. Results Tubal factors, including bilateral tubal blockage, were identified in 32% of cases, with a similar incidence in both primary and secondary infertility. Peritoneal factors, such as pelvic adhesions and endometriosis, were present in 24% of cases, predominantly in primary infertility. Diagnostic laparoscopy revealed a higher sensitivity for detecting these factors than HSG, emphasizing its role in cases where non-invasive imaging was inconclusive. Conclusion Diagnostic laparoscopy is a valuable tool for identifying tubal and peritoneal factors in female infertility, offering high diagnostic accuracy and aiding in tailored treatment planning. Its ability to directly visualize pelvic abnormalities makes it essential in the comprehensive evaluation of infertility. Recommendations Laparoscopy should be considered in routine infertility workups, especially for patients with unexplained infertility or inconclusive HSG results. Further research on combining laparoscopy with minimally invasive treatments may improve fertility outcomes.